KAJIAN AKTIVITAS ANTIOKSIDAN ALGA HIJAU Ulva lactuca DARI PERAIRAN PANTAI SUNDAK, GUNUNGKIDUL - Arianti, Dyah; Ibrahim, Ratna; Agustini, Tri Winarni (Jurnal Pengolahan dan Bioteknologi Hasil Perikanan, 2013)
This study aims to determine the polarity of bioactive compounds, compounds that act asantioxidants, the effects of different solvent polarity used on the process of macerationtoward the antioxidant activity, total phenolic, chlorophyll a, chlorophyll b and carotenoidcontents, and the correlation of each of them to the activity of free radical inhibition. Theresults showed that the highest antioxidant activity was obtained from sample which wasaxtracted by acetone solution which has IC50 value of 281.425 ppm. Bioactive compoundsthat act as antioxidants in the U. lactuca were semi polar. It was detected as alkaloids andphenols. The different polarity solvent which was used for maceration of sample caused thevalue of antioxidant activity differ significantly. The highest total phenolic, chlorophyll a,chlorophyll b, and carotenoid contents were obtained from the sample extracted by acetonsolution. Each of their values was 65.753 mg GAE/g sample, 2.547 mg/g sample, 1.996 mg/gsample, and 2.264 mg/g sample recpectively. Each of the value was positively correlated withfree radicals inhibition percentage.